PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN BERINDEKS LQ-45 YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2018-2022) - Widyastuti, Krisanti; Mulyani, Nani (Jurnal Nusa Akuntansi, 2024)
This research aims to analyze the influence of Institutional Ownership, Managerial Ownership and Capital Intensity on Tax Avoidance. This research was conducted by analyzing the financial reports of companies with the LQ-45 index listed on the Indonesia Stock Exchange (BEI) during the period 2018 to 2022. The sample used in this research was 13 companies with the LQ-45 index listed on the Stock Exchange Indonesian Effect (BEI) using a purposive sampling technique. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The panel data regression method was used as the research methodology in this study. Analysis of the results of this research using E-Views 12 Student Version Lite software. The results of this study show that Institutional Ownership partially has no effect on Tax Avodance, Managerial Ownership partially has an effect on Tax Avoidance, Capital Intensity partially has an effect on Tax Avoidance, and simultaneously Institutional Ownership, Managerial Ownership and Capital Intensity have an effect on Tax Avoidance.